Successful pancreatoduodenectomy of de novo duodenal malignancy after orthotopic liver transplantation: A case report - Ji, Linhua; Xu, Danhua; Zhu, Chunchao; Xu, Jia; Cao, Hui; Zhao, Gang (Frontiers in Surgery, 2023)
Introduction: liver transplantation is a risk factor for premalignant and malignant changes of the duodenum. De novo duodenal malignancy is seldom reported after liver transplantation. Case Report: The present study reports a case of an asymptomatic 65-year-old male patient who underwent liver transplantation more than 9 years ago and subsequently developed duodenal malignancy. Endoscopic biopsy of the de novo duodenal malignancy indicated duodenal carcinoma and pancreatoduodenectomy (PD) was performed. The patient was successfully discharged 12 days after the surgery. Conclusions: To the best of our knowledge, this case type has not been previously reported. The present study sheds light on the development, the treatment, the prognosis, and the management of a new type of de novo duodenal malignancy.